2009
DOI: 10.4103/1742-6413.53887
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the modified fluorescent method and conventional Ziehl–Neelsen method in the detection of acidfast bacilli in lymphnode aspirates

Abstract: Objectives:The objectives were to correlate the modified fluorescent method with the conventional Ziehl–Neelsen (ZN) method for the detection of acid-fast bacilli (AFB) and, also to study the efficacy and advantages of using the auramine–rhodamine stain on lymph node aspirates under fluorescent microscopy.Methods:In 108 consecutive patients with a clinical suspicion of tuberculosis (TB) presenting with lymphadenopathy, fine needle aspirations were performed. Smears from the aspirates were processed for routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 7 publications
5
26
1
Order By: Relevance
“…In present study maximum cases affected were in the age group of 21-30 yrs, which accounted for 56.92% (37/65) of total cases. The age group most commonly affected by tuberculosis in our study is correlated with other studies like Dagar et al [14] Annam et al [15]. In our study mean age was 28.5 years, Dagaret al [14] has also observed the similar mean age for diagnosis.…”
Section: Original Research Articlesupporting
confidence: 91%
See 1 more Smart Citation
“…In present study maximum cases affected were in the age group of 21-30 yrs, which accounted for 56.92% (37/65) of total cases. The age group most commonly affected by tuberculosis in our study is correlated with other studies like Dagar et al [14] Annam et al [15]. In our study mean age was 28.5 years, Dagaret al [14] has also observed the similar mean age for diagnosis.…”
Section: Original Research Articlesupporting
confidence: 91%
“…Shows cytological criteria for the diagnosis of tubercular lymphadenitis [4]. Conventional Ziehl-Neelsen (ZN) method for acidfast bacilli (AFB) plays a key role in the diagnosis and the monitoring of treatment in tuberculosis [5]. Fluorescent microscopy using auramine-rhodamine (AR) staining is rapid, simple, easy method with high detection rate for AFB as compared to ZN method [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Culture is essential for a definitive diagnosis; however, it takes weeks for identification, and its sensitivity is also relatively low in paucibacillary conditions [5, 6]. Conventional Ziehl-Neelsen (ZN) method for acid-fast bacilli (AFB) plays a key role in the diagnosis and the monitoring of treatment in tuberculosis [7]. Its major disadvantages are low sensitivity, time consuming, and oil immersion use.…”
Section: Introductionmentioning
confidence: 99%
“…Ziehl-Nelson (ZN) staining -ZN staining is an essential diagnostic tool for the identification of AFB and the evaluation of treatment outcome in TB [16]. Bright red rods against blue, green or yellow background are characteristic of AFB [3] (Fig.…”
Section: Smearsmentioning
confidence: 99%